Serving families who face economic and related adversities: the ‘5 As’ of effective ECEC service delivery - Skattebol, Jennifer; Adamson, Elizabeth; Blaxland, Megan (Frontiers in Education, 2023)
Families with young children who face economic and related adversities are the most likely group to miss out on the advantages of regular sustained participation in high quality early childhood education and care. In Australia, there are an estimated 11% of children assessed by teachers to have two or more developmental vulnerabilities and many of these children are living in economically disadvantaged contexts (Commonwealth of Australia, 2022). Government policy in Australia aspires to provide universal access to Early Childhood Education and Care (ECEC) services to support children’s outcomes and ensure workforce participation, but policy falls short of ensuring all families can take up high quality early childhood education and care. Government responses to the Covid crisis saw significant changes to the ECEC policy and funding mechanisms. It is timely therefore to reflect on the level of ‘competence’ in the Australian ECEC systems. Urban et al. (2012) coined this term to refer to a system that is sustainable, inclusive, and effective for all families. We have taken up the challenge of considering the Australian system in terms of inclusivity for families who typically find services hard to use. We used a Delphi methodology to coalesce the insights of high-level stakeholders who have expertise in delivering services to these families and noted points of consensus and of divergence among these stakeholders. We put forward a model that frames the characteristics of services that can inclusively engage with families - Approachable, Acceptable, Affordable, Accessible and Appropriate. We argue that more needs to be known about appropriateness and what effective pedagogy looks like on the ground for families and children.